Vrouwen Wereldwijd - Brekke, Toril; Davis, Angela; Taylor, Debbie (Amsterdam: Feministische uitgeverij Sara, 1985)
"Toril Brekke, Angela Davis, Debbie Taylor... et al. Oorspronkelijke titel : Women : a world report"